From statutory to private contracts: Emerging institutional arrangements in the smallholder tea sector in Malawi - Kydd, Jonathan G.; Chirwa, Ephraim (International Food Policy Research Institute, 2009)
This case study addresses the issues of institutional change and the need for collective action in a commodity, tea, which requires high fixed investment in processing facilities. In the wake of political and economic changes, the case study illustrates how asset specificity and commodity characteristics facilitate vertical integration as discussed in Chapter 5 and how exogenous changes have influenced institutional arrangements and contract enforcement in the Malawian tea industry. The case study raises such issues in contract farming as enforcement of contracts and compatible incentives when the state is a major player, and it shows the consequences of state failure, an issue that is discussed further in Chapter 20.